Clinical and echo cardiographic profile of aortic valve stenosis in patients of north Kerala - Kunnummal, Anoopkumar; Pariyapurath, Rosh; Puzhangattil, Shanavas; Krishnan, Vinod; Vijayakumar, Neenu; Gopal, Ajesh (International Journal of Research in Medical Sciences, 2016)
Background: An increase in the number of ageing population has led to a rise in the incidence of aortic stenosis. The study aims to analyze the clinical profile, echocardiographic features and common associations of aortic valve stenosis in patients of north Kerala. Methods: This study included73 adult patients with clinical manifestation and echocardiographic evidence of aortic stenosis, who attended the department of general medicine in a tertiary care centre, Kerala, south India over a period of one year. Results: 63% of patients were males and 58% of patients were between 50 to 60 years. 85% had severe aortic stenosis, 43% were hypertensive and 20% were diabetic.12% had ischemic heart disease. Rheumatic heart disease was seen in about 7% of patients. On analysing LV dimensions it was found that females have lower LV volumes when compared to males. Females had low ejection fraction and higher peak gradients. About 20% had bicuspid aortic valves. Conclusions: Age, gender, smoking, hypertension and diabetes had no statistically significant association with severity of aortic stenosis in this population. Aortic stenosis due to Rheumatic etiology and that due to bicuspid valve presented at an early age. Adaptive mechanisms to aortic stenosis may be different in two sexes.